The path toward a cloud‐aware mobile network protocol stack. Issue 5 (19th April 2018) - Serrano, Pablo; Gramaglia, Marco; Bega, Dario; Gutierrez‐Estevez, David; Garcia‐Aviles, Gines; Banchs, Albert
Abstract: We are currently observing the softwarization of communication networks, where network functions are translated from monolithic pieces of equipment to programs running over a shared pool of computational, storage, and communication resources. While it is clear that almost any softwarization improves flexibility (eg, the ability to instantiate more servers to cope with increasing traffic demand), in this paper, we advocate for a complete redesign of the communications protocol stack, instead of a mere translation of hardware functions into software. We discuss 2 drivers for this cloud‐aware redesign: (1) relaxing the tight interactions between functions and (2) supporting a graceful degradation of the service when resources become scarce. The potential benefits of this redesign are illustrated with the numerical evaluation of one use case. Abstract : This paper discuss about the challenges that future, cloudified network will need to solve in order to be cloud‐aware. Specifically, we identify two research problems (re‐thinking VNF interaction and re‐designing VNF internals) and provide initial solutions for them.